ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS PADA WP OP YANG TERDAFTAR DI KPP PRATAMA JAKARTA KELAPA GADING) - Nadya Sheila Noviyani ; Drs. Nasikin, Ak., MM
This research hs the aim to examine empirically the effect of taxpayers awareness, service quality of tax authorities, communication about taxes, and tax penalty on the compliance of individual taxpayers registered at the Kelapa Gading Small Tax Office (KPP Pratama), Jakarta. The independent variables of this research are taxpayers awareness, service quality of tax authorities, communication about taxes, and tax penalty, while the dependent variable is taxpayers compliance. This research is a quantitative research and the data was collected using the survey method. The samples were taken by simple random sampling method. The number of taxpayers that parcitipated in this study was 100 respondents. The utilized statistical method is Multiple Linear Regression Analysis. The data was processed using the Statistical Package for the Social Sciences (SPSS) program. The results of this study indicated that taxpayers awareness, service quality of tax authorities, communication about taxes, and tax penalty have a positive influence on taxpayers compliance. _x000D_ _x000D_ Keywords: taxpayers compliance, taxpayers awareness, service quality of tax authorities, tax socialization, and tax penalty.